The Ministry of Agriculture and Rural Development incorporated A4NH evidence in implementation of nutrition-sensitive agriculture approaches in Viet Nam as part of their National Action Plan for Zero Hunger - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The Ministry of Agriculture and Rural Development (MARD) implemented A4NH-informed nutrition-sensitive agriculture approaches in 11 provinces in Viet Nam as part of their Zero Hunger initiative. The food systems framework, developed by A4NH researchers, was included in the training materials for provincial staff. In addition, A4NH-informed training materials were approved by MARD as key resources for implementation. These contributions were possible because the A4NH Country Coordinator is an invited member of the Zero Hunger technical group and approval committees.